PREDICTION ANALYSIS OF DIVORCE RATE USING THE DECISION SUPPORT SYSTEM METHOD - Shary Armonitha; Nugraha Rahmansyah (Jurnal Ipteks Terapan (Research Of Applied Science And Education ), 2022)
The existence of divorce actually results in the separation of husband and wife bonds. This study aims to examine and examine the influence of divorce factors in the city of Padang. In this problem, the author predicts the divorce rate that will occur in the city of Padang in 2021 by reviewing divorce data in 2020. The method used in this study is normative juridical research by conducting observations, field notes, and interviews with related parties at the research location. . The results of this study will provide benefits for the Padang Class IA Religious Court to make a breakthrough that is able to reduce the divorce rate. The analysis in this problem also uses two methods of decision support systems, namely Single Moving Average (SMA) and Analytical Hierarchy Process (AHP). Based on manual calculations, the researcher can conclude that continuous disputes in the household can trigger divorce. Therefore, the Padang Class IA Religious Court can make a breakthrough in the form of education about the impact of divorce and education in solving a problem. The application of the Single Moving Average method can predict accurately for January 2021 as many as 96 cases for 5 period predictions with a MAPE of 11%. In the calculation of the Analytical Hierarchy Process method, the final calculation is 0.32 which shows that continuous disputes can lead to divorce.